Robust nonlinear observer design for actuator fault detection in diesel engines - Boulkroune, Boulaid; Djemili, Issam; Aitouche, Abdel; Cocquempot, Vincent (Zielona Góra: Uniwersytet Zielonogórski)
This paper is concerned with actuator fault detection in nonlinear systems in the presence of disturbances. A nonlinear unknown input observer is designed and the output estimation error is used as a residual for fault detection. To deal with the problem of high Lipschitz constants, a modified mean-value theorem is used to express the nonlinear error dynamics as a convex combination of known matrices with time-varying coefficients. Moreover, the disturbance attenuation is performed using a modified H[the sign of infinity] criterion.
Keywords: Diesel engine; fault diagnosis; nonlinear unknown input observers; LMI